PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI KELAS XII MIPA SMA NEGERI 2 GUNUNG TALANG - Zuriyati, Zuriyati (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematical comprehension is essential. Due to low student engagement, class XII MIPA at SMA Negeri 2 Gunung Talang pupils' understanding is still poor. To solve this, inquiry learning was used. This study examines students' mathematical concept understanding after using the inquiry model and whether inquiry-based learning is better than conventional learning. This study used a nonequivalent posttest-only control group design and quasi-experimental and descriptive research. XII MIPA students of SMA Negeri 2 Gunung Talang in 2023/2024 were the research sample. Data research demonstrated that inquiry learning students understood mathematical concepts better than standard learners. In addition, the inquiry methodology improves students' subject knowledge.Keywords – Conventional Learning, Inquiry Model, Undertanding Mathematical Concepts